Kochia scoparia response to dicamba and effective management practices for soybeans - Brachtenbach, David A. (Kansas State University, 2015)
Kochia [Kochia scoparia (L.) Schrad.] is an invasive weed that is common in cropland, pastures and rangeland, rights-of-way, and disturbed areas throughout the western and northern United States and southern Canada. This species aggressively competes with crops, especially in no-till cropping systems, and has evolved resistance to multiple herbicide modes of action. Thus, it has become highly problematic and is difficult to manage. Roundup Ready 2 Xtend™ (Monsanto Co.) soybeans with resistance to dicamba herbicide are expected to be commercialized in 2016, and will offer a new management practice for controlling kochia and other susceptible broadleaf weeds in soybeans. Objectives of this research were to (1) determine whether greenhouse-grown plants from various kochia populations from the central Great Plains differ in susceptibility to postemergence-applied dicamba; (2) compare preemergence versus postemergence control of kochia with dicamba in a greenhouse environment; and (3) investigate various management practices in a systems approach to control kochia in soybeans. GR[subscript]50 values (dose required to reduce plant biomass by 50%) indicated at least an 8-fold difference among 11 kochia populations in susceptibility to postemergence-applied dicamba. Additionally, dicamba at 210 g ha[superscript]-1 applied preemergence caused 95, 88 and 84% mortality and reduced plant biomass (fresh wt.) of the most susceptible and two least susceptible kochia populations from a previous dicamba dose-response study by 99, 68 and 60%, respectively. In comparison, <10% of kochia plants from those populations died and biomass was reduced only 39, 15 and 7%, respectively, when dicamba was applied postemergence. Field experiments demonstrated that preplant conventional tillage followed by nine different in-crop herbicide treatments, and shallow early-spring tillage followed by preplant herbicides (reduced-till) along with the same in-crop herbicides provided greater kochia control than three no-till systems involving early preplant herbicide treatments followed by the same in-crop herbicides. However, despite greater kochia control with the tillage-based systems in 2013, soybean yields were less compared to the three no-till systems. Consequently, in some years the most effective kochia control practices may not result in the highest soybean yields.
Keywords: Kochia; Dicamba; Dicamba preemergence; Management practices for soybeans; Agronomy (0285)